Agricultural development strategies in Asia : - Ishikawa, Chigeru (Asian Development Bank, 1970)
The concept of the surplus was developed by Paul Baran in The Political Economy of Growth (1968) as a distinct category of economic analysis. He argued that by examining which classes received the surplus and the manner in which they disposed of it, the forces creating and perpetuating underdevelopment could be understood. His insights on the critical role of class structure and surplus use in underdeveloped countries have never been properly followed up, however, in part because of confusion and inconsistencies in his own presentation. This essay attempts to clarify the concept of the surplus and to show how it can be used, in conjunction with the analysis of class structure, in theoretical and empirical analyses of economic development.